Postoperative Atrial Fibrillation after Coronary Artery Bypass Grafting Surgery: A Two-dimensional Speckle Tracking Echocardiography Study - ÖZBEN SADIÇ, BESTE; FİLİNTE, DENİZ; SARI, İBRAHİM; AK, KORAY; SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT (ELSEVIER SCIENCE INC, 2016)
Background Postoperative atrial fibrillation (POAF) may develop after coronary artery bypass grafting (CABG). The aim of the study was to explore the relationship between preoperative left atrial function and atrial fibrosis and POAF after CABG. Methods Forty-eight consecutive patients undergoing CABG (mean age: 61.6 +/- 8.9 years, 39 male) were included. All patients were in sinus rhythm during surgery. Patients were followed by continuous electrocardiography monitoring and daily electrocardiogram. Left atrial function was assessed by both conventional and speckle tracking echocardiography. Atrial fibrosis was determined by samples taken from right atrium. Results Postoperative atrial fibrillation was detected in 13 patients. Female sex and number of bypassed vessels were significantly higher and cardiopulmonary bypass time was significantly longer in patients with POAF. Left atrial volume index (LAVI) was significantly higher while left atrial reservoir strain was significantly lower in POAF patients. The percentage of patients with severe fibrosis was higher in the POAF group. Regression analysis revealed fibrosis and LAVI as independent predictors of POAF. Left atrial volume index >= 36 mL/m(2) predicted POAF with a sensitivity of 84.6% and specificity of 68.6% in our cohort. Conclusion Patients who developed POAF after CABG had more fibrosis, increased LAVI and lower left atrial reservoir strain. Preoperative echocardiography might be helpful in discriminating these patients.
Keywords: Postoperative atrial fibrillation; Coronary artery bypass; Fibrosis; Speckle tracking imaging; STRAIN-RATE; VENTRICULAR DYSSYNCHRONY; CARDIAC-SURGERY; RISK; PREDICTS; DYSFUNCTION; MORTALITY; VOLUME